A comparasion between artificial intelligence and radiologists in the field of interpretation of image exams (Research, Society and Development, 2024)
In the field of imaging interpretation, radiologists combine clinical and technical expertise to achieve an accurate diagnosis. On the other hand, artificial intelligence (AI) can process and combine large volumes of data. In addition, it is questioned what would be the role of AI in the field of radiology when compared to radiologists. The present study seeks to make a comparison between artificial intelligence and radiologists in the field of interpretation of imaging exams by means of a literature review, which used the PubMed, SciELO and Fiocruz databases as research means. There are studies that prove that currently some artificial intelligence databases based on "deep learning" are still not sufficient to achieve diagnostic imaging results higher than 80% sensitivity, taking as a comparison the sensitivity of standard exams without artificial intelligence interpretation. The conclusion was that there are indications that AI can achieve levels of accuracy similar to or higher than those of radiologists under certain conditions. However, the joint participation between humans and artificial intelligence increases the sensitivity of imaging exams, as well as accuracy.